Problems of Translating into Russian CZE-KA-NIE-NA-SCHO-DACH by Joanna Ślósarska - Bednarczyk, Anna (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2024)
This article examines the problems of translating into Russian the volume CZE-KA-NIE-NA-SCHO-DACH by Joanna Ślósarska , as well as the titular poem from this collection. The source material is treated as a cycle, which influences both the choice of translational dominant and subsequent decisions regarding translation methods and techniques used by the translator. The article addresses the issue of translating a polysemiotic text, which, in this case, combines verbal text and graphics. Starting from an analysis of the volume, highlighting the general difficulties of translation related to elements in the poems characteristic of Ślósarska, the author turns to a specific poem and discusses it in the context of the entire cycle. This analysis leads to the conclusion that translating free verse does not pose fewer challenges for the translator than translating verse based on a metrical system. The most significant translational challenge is shown to be the differences in language structures and intertextual references. On the other hand, similarities in literary systems are also noted, which facilitate the translation process.